(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The following issues are analyzed in this article: The principles of the formation of artistic psychology in world and Uzbek literary studies, the psyche of the hero in the works of the American writer Ray Bradbury and the Uzbek writer Hojiakbar Shaikhov were scientifically and theoretically analyzed. In the new century, we can see bright examples of psychologism in the works of Ray Bradbury and Hojiakbar Shaikhov. The reason for choosing these two authors as the object of research is that R. Bradbury will serve as a unique school in the formation of the science fiction genre at the world level, in the development of Uzbek fiction, and in the improvement of the work of the Uzbek science fiction writer H. Shaykhov. The article analyzes the story of Ray Bradbury’s novel "Fahrenheit 451" "Ice and Fire" and Hojiakbar Shaikhov’s "Connected Worlds". The evaluation of Shaikhov’s work in literary studies and the common and unique aspects of the hero’s psyche in the works of two writers are analyzed in a comparative aspect.